2009
DOI: 10.2114/jpa2.28.199
|View full text |Cite
|
Sign up to set email alerts
|

Age and Sex Differences of Controlled Force Exertion Measured by a Computer-generated Sinusoidal Target-pursuit System

Abstract: This study examined age and sex differences of controlled force exertion in 207 males and 249 females aged 15 to 86 years. The subjects matched the submaximal grip strength of their dominant hand to changing demand values, appearing as a sinusoidal waveform on the display of a personal computer. The total difference (%) between the demand value and the grip exertion value for 25 sec was used as an evaluation parameter. Significant linear regressions were identified, but there was no significant difference in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
0
9
1
Order By: Relevance
“…The cerebellum is thought to serve as a comparator for the actual movement that is occurring and the intended movement and is also used in the processing of visual feedback (Ghez and Thach, 2001). Previous studies of age related changes in grip force control have shown increased variability of force production (Nagasawa and Demura, 2009) and increased reliance on visual feedback in older adults (Sosnoff and Newell, 2007). These changes in force variability and visual processing could explain the higher levels of activity within the cerebellum for the older group.…”
Section: Discussionmentioning
confidence: 88%
“…The cerebellum is thought to serve as a comparator for the actual movement that is occurring and the intended movement and is also used in the processing of visual feedback (Ghez and Thach, 2001). Previous studies of age related changes in grip force control have shown increased variability of force production (Nagasawa and Demura, 2009) and increased reliance on visual feedback in older adults (Sosnoff and Newell, 2007). These changes in force variability and visual processing could explain the higher levels of activity within the cerebellum for the older group.…”
Section: Discussionmentioning
confidence: 88%
“…Thaweewannakij et al [20] reported that healthy elderly males perform better in the 10-m obstacle walking time, Berg balance scale, and 6-min walking tests than females for all age groups. Males generally perform better in grip strength, while females perform better in the sitting trunk flexion test [21,22]. Similar gender differences are also found in the standard values, because the results for grip strength, 10-m obstacle walking time, one-legged balance with eyes open test, situps, and 6-min walking tend to be higher in males whereas those for sitting trunk flexion values are higher in females (see Table 1).…”
Section: Gender and Age-related Differences In Physical Function Of Tmentioning
confidence: 65%
“…The cerebellum is generally associated with skilled motor movements, and the basal ganglia, in particular, the striatonigral system is associated with gross motor behavior [23]. Reports by several researchers [1,17,18] confirm that aged-related differences in CFE are greater with pursuit movements, and CFE ability decreases with age. In the present study, tests were performed with submaximal muscular exertion with a moderate cycle (0.1 Hz) of changing demand value.…”
Section: Resultsmentioning
confidence: 97%
“…No significant differences were found for CFE scores in the three groups. Nagasawa and Demura [18] reported that in individuals aged more than 50 years, CFE measured by the sinusoidal waveform shows a marked decrease. In the young-aged group in our study, the insignificant correlation between CFE and the maximum grip strength indicated that this group of participants experienced a similar difficulty with respect to CFE that is not dependent on the magnitude of force output.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation